The effectiveness of peat water media that is fermented slaughterhouse liquid waste for growing Spirullina sp. - Ersyam, Taslima Fauzanah; Budijono, Budijono; Harahap, Sampe (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTSlaughterhouse liquid waste contains fair organic materials that can be used as nutrient source for growing Spirulina sp. The purpose of this study was to determine the effect of fermented slaughterhouse waste as alternative nutrients for the growth of Spirulina sp. This study was conducted in September-October 2019. RAL method was applied with 5 different concentrations, there were 0 ml/4L (P0), 400 ml/4L (P1), 800 ml/4L (P2), 1,200 ml/4L (P3) and 1,600 ml/4L (P4), with 3 repetitions. Parameters measured were Spirulina sp. abundance, nitrate and phosphate content. Results shown that Spirulina sp. grow well in all treatments, except in control. The best result was provided by P3 (4,907 x 103cells/ml) that was achieved on the 9th day. Nitrate and phosphate content decreased during the experiment, the nitrate was reduced by 5.2091 mg/L or 87.2 %, while the phosphate was reduced by 18.784 mg/L or 84.1 %. Based on data obtained, it can be concluded that the peat water can be enriched by addition of fermented slaughterhouse waste and it can be used as nutrients for growing Spirulina sp. Keywords: nutrient, liquid waste, microalgae, algae culture